Effect of Time of Cord Clamping on the Serum Bilirubin Level among Full-Term Babies Born in an Ethiopian Hospital Setting: An Exploratory Three-Arm Randomized Controlled Trial - Biruk Hailu Tesfaye; Mulugeta Betre Gebremariam; Abiy Seifu Estifanos; Asrat D. Gebremedhin (International Journal of Clinical Practice)
Background. Delayed cord clamping (DCC) for more than one minute is associated with nutritional and developmental benefits for newborns. However, there is limited evidence regarding the relationship between DCC and outcomes in resource-limited settings. This study aims to assess the effect of the time of cord clamping on serum bilirubin level 24 hours after birth in an Ethiopian Tertiary Care hospital. Methods. A three-arm, single-blind, exploratory randomized controlled trial was conducted between October 2019 and January 2020 targeting healthy, full-term neonates. Study participants were randomly assigned into one of the following intervention groups depending on the timing of cord clamping: immediate cord clamping (<30 seconds), intermediate cord clamping (60 seconds), and DCC (180 seconds). The primary outcome is serum bilirubin level in the newborns, which was assessed 24 hours after birth and before they were discharged home. Descriptive analysis was applied to assess differences between groups in terms of demographic, obstetric, and social characteristics of the participants, while a linear regression model was employed to examine the association between cord clamping time and serum bilirubin level. Result. A total of 141 term newborns were included and randomized into the three categories. The demographic, social, and obstetrics characteristics of included participants were not different across groups except for the labor duration (P value <0.05). While the time of cord clamping was not a significant predictor of total serum bilirubin levels at 24 hours postbirth, cord blood total serum bilirubin (coefficient: 0.24; p<0.05) and bilirubin nomogram high-risk zone (coefficient: 6.25; p<0.001) were found to be significant predictors. (4) Conclusion. Our findings indicate that the time of umbilical cord clamping does not affect the total serum bilirubin level of neonates at least within 24 hours of birth.